2021
DOI: 10.3390/plants10020258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plant Morphology, Yield and Nutritional Quality of Fagopyrum esculentum and Fagopyrum tataricum Grown under Field Conditions in Belgium

Abstract: Buckwheat is a pseudocereal with high nutritional and nutraceutical properties. Although common buckwheat (Fagopyrum esculentum) is the main cultivated species, Tartary buckwheat (Fagopyrum tataricum) is gaining interest. In this paper, we compared plant growth, yield-related parameters and seed nutritional qualities of two varieties of F. esculentum and F. tataricum under field conditions in Belgium. Fagopyrum esculentum flowered earlier, produced less nodes, less branches, less inflorescences, but more flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 35 publications
(79 reference statements)
7
24
1
Order By: Relevance
“…In this study we measured the concentrations of the nine elements in the buckwheat whole grains samples, and we found significant differences in the Cu, Mn, Fe, Zn, Mg, Ca, Na, K, and P contents of the buckwheat samples. Of the measured minerals, K was the most abundant macroelement in the buckwheat grains, which is confirmed in studies [ 23 , 28 , 31 , 32 , 33 ]. In this study, we found differences between tested genotypes in mineral content.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In this study we measured the concentrations of the nine elements in the buckwheat whole grains samples, and we found significant differences in the Cu, Mn, Fe, Zn, Mg, Ca, Na, K, and P contents of the buckwheat samples. Of the measured minerals, K was the most abundant macroelement in the buckwheat grains, which is confirmed in studies [ 23 , 28 , 31 , 32 , 33 ]. In this study, we found differences between tested genotypes in mineral content.…”
Section: Discussionsupporting
confidence: 77%
“…Guo et al [ 7 ] reported that rutin content in tartary buckwheat ranges from 2077 to 3149 μmol /100 g DW. In our experiment, the rutin level in F. tataricum seeds was 15 times higher, while in Aubert et al [ 23 ] experiment was 60 times higher. We found differences between cultivars of the same species for the rutin content.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…It is also more drought resistant than common buckwheat. Indeed, Tartary buckwheat has traits of drought tolerance, while common buckwheat has properties of drought avoidance [9].…”
Section: Introductionmentioning
confidence: 99%